Pemanfaatan Media Audio Visual Sebagai Sumber Belajar Sejarah Di Madrasah Aliyah Tahfizhil Qur’an - Albert Christian Christian; Enisya Putri Surya; Meliani Br Sembiring; Mhd Ihsan Syahaf (BEST Journal (Biology Education, Sains and Technology), 2022)
Advances in science and technology, especially information technology, greatly influence the preparation and implementation of learning strategies. Media is an intermediary such as TV, radio, slides, printed materials, but includes people or humans as a source of learning or in the form of activities including discussions, seminars, field trips, simulations and so on that are conditioned to add and insight, change student attitudes to increase knowledge. This research uses qualitative descriptive research methods with research locations in madrasah Aliyah Tahfizhil Qur'an. The main subjects in this study are history teachers and students at Madrasah Aliyah Tahfizhil Qur'an who teach focusing on learning activities about Indonesian History material by utilizing audio visuals in history learning. Based on the results of research and discussion on the use of audio-visual media in learning Indonesian History class XI social studies Madrasah Aliyah Tahfizhil Qur'an. Learning attracts more students' attention so that it can foster learning motivation, learning materials become clearer in meaning, making it easier for students to understand learning. And students do more learning activities, because not only listening to the teacher's description, they do other activities such as observing, doing, demonstrating.